Thermoelectric Coolers for X-ray Detectors - Anatychuk, L.I.; Prybyla, A.V. (Science and Innovation, 2024)
Introduction. X-ray methods are widely used for the nondestructive microanalytic studies of the structure and composition of materials with a high spatial resolution. Further increase in their resolution depends substantially on improving the analytical characteristics of semiconductor detectors, as well as on the application of novel types of wide-aperture position-sensitive radiation detectors. Problem Statement. The resolution of X-ray detectors is essentially dependent on their operating temperature mode, provided by the use of thermoelectric coolers. single-stage thermoelectric coolers (TeC) are used for superficial cooling (down to 250K); to cool sensors to an operating temperature of 230K two-stage TeCs are used and three-stage TeCs are used for temperatures down to 210K, whereas four- and five-stage ones are meant for cooling below 190K. Purpose. Design and structural optimization of a thermoelectric multi-stage cooler of X-ray radiation detector. Materials and Methods. Computer-based object-oriented design methods and optimal control theory methods adapted for thermoelectric energy conversion applications. To develop thermoelectric cooling modules, bismuth telluride-based materials (Bi2Te3) of n- and p-types of conductivity have been used. Results. Calculations of the design of the thermoelectric cooler as a part of the X-ray detector showed optimum electric power of the thermoelectric converter W=2.85W, which, with a refrigeration coefficient e=0.02, provides the detector base temperature Tc=-70°C and ∆T=90K. These temperature conditions are optimal for the operation of X-ray detectors and can significantly increase their resolution with minimal electricity consumption. Conclusions. A comprehensive study and optimization has been performed, and the design of a thermoelectric multistage cooler has been calculated, which ensures optimal operating conditions for the X-ray detector. The obtained results can be used to create X-ray detectors with high resolution.